Cultural Content Integration in EFL: Examining Pre-Service Teachers’ Material Development - Luluk Ambarwati; Noni Agustina (EduInovasi: Journal of Basic Educational Studies, 2026)
Language learning cannot be separated from cultural elements, because besides serving as a means of communication, language also reflects social practices, values, and perspectives. Integrating cultural content into English as a Foreign Language (EFL) learning materials is crucial for improving students’ intercultural skills and equipping them with the skills to build good communication in various contexts. However, previous research has revealed that cultural content is underrepresented or often neglected in language learning, where linguistic competence is emphasized over reflecting culture. This study aims to examine the extent to which pre-service teachers integrating cultural content, including source culture, target culture, and international culture, into the EFL materials they develop. This study uses a qualitative design with content analysis methods to analyze how culture is represented in English as a foreign language (EFL) learning. This study analyzed English language learning materials developed by pre-service teachers for phases A, C, D, E, and F. The results showed that the English language learning materials developed by pre-service teachers mostly discussed the source culture and neglected international culture. The imbalance in the representation of cultural content in English language learning materials can affect students' intercultural skills. This study suggests the need for future research to examine cultural themes depicted in English language learning materials developed by pre-service teachers using different cultural frameworks.